2016
DOI: 10.1002/2327-6924.12253
|View full text |Cite
|
Sign up to set email alerts
|

Medication use and predictors of sexual activity in men and women with CVD

Abstract: Purpose To examine the influence of cardiac and noncardiac medications on sexual activity by drug classification and generation of the drug, among men and women with cardiovascular disease. Data sources This study was a subanalysis (n = 224) of survey data from a cross‐sectional sample of 336 cardiac patients. Self‐reported medications were categorized by generic drug name, classification, and subclass and/or generation of the drug. Sexual activity was the presence or absence of current sexual activity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Strippoli et al 40 , studying 1472 women with end-stage renal disease who were undergoing dialysis, found that diuretic use was associated with sexual dysfunction as assessed with the FSFI. In particular, thiazide diuretic use is postulated to be associated with decreased libido and vaginal lubrication 41 . However, as the authors state, future research is needed to determine whether diuretic treatment in CKD patients is directly associated with sexual dysfunction, or whether it reflects comorbidity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Strippoli et al 40 , studying 1472 women with end-stage renal disease who were undergoing dialysis, found that diuretic use was associated with sexual dysfunction as assessed with the FSFI. In particular, thiazide diuretic use is postulated to be associated with decreased libido and vaginal lubrication 41 . However, as the authors state, future research is needed to determine whether diuretic treatment in CKD patients is directly associated with sexual dysfunction, or whether it reflects comorbidity 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The experience of living with CADs is associated with a variety of consequences that influence patients' sexual health [9]. Patients with CADs complain of different sexual health problems including decrease of sexual activities, interest in sex and level of sexual satisfaction [10], physical discomfort during sexual activities [11], and alterations in both frequency and quality of sexual activity [12].…”
Section: The Cads and Sexual Healthmentioning
confidence: 99%
“…While medications are conventionally known to contribute to sexual problems and changes in sexual activity patterns, the effects of cardiac medications on sexual function are restricted to a few drugs which have been identified as causing erectile dysfunction. Diuretics, particularly thiazides, are the drugs most strongly linked to sexual dysfunction, both in men and women, causing impotence, decreased libido and erectile dysfunction 8. β-blockers are probably the best known drug class deemed capable of inducing sexual disorders.…”
Section: Discussing Sexual Activitymentioning
confidence: 99%
“…β-blockers are probably the best known drug class deemed capable of inducing sexual disorders. However, this was mainly the case with the older generation of β-blockers given to men 8. Use of more recent β-blockers, such as nebivolol, has been shown to affect sexual function positively 8.…”
Section: Discussing Sexual Activitymentioning
confidence: 99%
See 1 more Smart Citation